Site-specific analysis of protein hydration based on unnatural amino acid fluorescence - Amaro, Mariana; Brezovský, Jan; Kováčová, Silvia; Sýkora, Jan; Bednář, David; Němec, Václav; Lišková, Veronika; Kurumbang, Nagendra Prasad; Beerens, Koen; Chaloupková, Radka; Paruch, Kamil; Hof, Martin; et al. (Journal of the American Chemical Society, 2015)
Hydration of proteins profoundly affects their functions. We describe a simple and general method for site-specific analysis of protein hydration based on the in vivo incorporation of fluorescent unnatural amino acids and their analysis by steady-state fluorescence spectroscopy. Using this method, we investigate the hydration of functionally important regions of dehalogenases. The experimental results are compared to findings from molecular dynamics simulations.
Keywords: voda; Water; Molecular Structure; Fluorescence; Proteins; molekulární struktura; Molecular Dynamics Simulation; aminokyseliny; proteiny; Amino Acids; simulace molekulární dynamiky; fluorescence